An Analysis of Gender Representation in Bilingual Textbook ‘Little Sunshine’ - Sulalah, Anis (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates gender representation within the ‘Little Sunshine Bilingual Textbook’ (Setyaningrum et al., 2018), specifically examining grammatical equivalence in translating Indonesian pronouns and nouns into English. Employing a qualitative methodology with a naturalistic approach, the research utilizes corpus tools to categorize masculine and feminine terminology across three analytical levels. Findings reveal a significant gender disparity and visibility bias within the text, as male-oriented terms predominantly surpass female equivalents. Furthermore, the analysis demonstrates a systematic preference for masculine descriptors when translating the Indonesian gender-neutral third-person singular pronoun. These results underscore the presence of gender discrimination and linguistic asymmetry in bilingual educational materials. The study concludes that such translation choices reflect and reinforce traditional gender hierarchies, necessitating a more balanced approach in pedagogical content.